2022
DOI: 10.3846/ijspm.2022.17588
|View full text |Cite
|
Sign up to set email alerts
|

Research on Property Service Mode Innovation in the Context of Transformation and Upgrading

Abstract: Property service mode innovation is the basic means of property service enterprise management. Discussing the property service mode in terms of transformation and upgrading is of rich research significance, taking Wenzhou Sapphire Property Service Co. LTD. in China (hereafter referred to as “Sapphire Service”) as an example. First, based on the development of property service in China, this paper summarizes the 4E mode of traditional property service, ensuring cleaning, ensuring greening, ensuring maintenance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Literature [9] explored the coupled development relationship between the modern producer service industry and tourism enterprises, based on the deep agglomeration of producer service industry can help tourism enterprises better optimize their eco-efficiency, and used the actual data to carry out the correlation test analysis. Literature [10] takes the Sapphire Service Company as a research example, analyzes the path of property service common mode innovation for property service management in the modern service industry, which needs to be fully integrated with the development needs of the property service industry, and constructs a new 4R model for modern property service, which promotes the innovative development of the property service management mode.…”
Section: Review Of Relevant Research Work 1) Development Of Modern Se...mentioning
confidence: 99%
See 1 more Smart Citation
“…Literature [9] explored the coupled development relationship between the modern producer service industry and tourism enterprises, based on the deep agglomeration of producer service industry can help tourism enterprises better optimize their eco-efficiency, and used the actual data to carry out the correlation test analysis. Literature [10] takes the Sapphire Service Company as a research example, analyzes the path of property service common mode innovation for property service management in the modern service industry, which needs to be fully integrated with the development needs of the property service industry, and constructs a new 4R model for modern property service, which promotes the innovative development of the property service management mode.…”
Section: Review Of Relevant Research Work 1) Development Of Modern Se...mentioning
confidence: 99%
“…Xiaobin Xu, Ruiye Zhao. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] …”
unclassified
“…The higher the number and efficiency of matching, the greater the income of intermediary. However, if the income obtained by matching is lower than that obtained by crowding the interests of both matching parties, the intermediary may take risks for its own benefit (Liu et al, 2022;Suzuki & Shibata, 2022;Sladić et al, 2021). At the same time, customer portraits and product descriptions have become an important part of the bilateral matching of property transaction.…”
Section: Introductionmentioning
confidence: 99%
“…A common assumption proposed in most prior studies was that the demanders and suppliers were able to express their opinions or perceptions using numerical values. In many realistic situations, however, people usually describe their opinions with linguistic assessments rather than numerical values (Wang & Chuu, 2004;Yu et al, 2021Liu et al, 2022). Different attributes or characteristics should be expressed in different types of data forms, only that can reflect the characteristics of customers or property to the greatest extent.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of real estate management has a shorter history compared to management of production processes (Muczyński, 2015). It is only over the last few decades, research has shown an increase in real estate management topic (Liu et al, 2022). For an extended period, according to Muczyński (2015), properties were essentially regarded as objects facilitating the production, storage, sale, or utilization of objects.…”
Section: Introductionmentioning
confidence: 99%